2016
DOI: 10.1590/1981-6723.9715
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and antioxidant composition of fresh peach palm (Bactris gasipaes Kunth) fruits in Costa Rica

Abstract: SummaryThe variability of the physicochemical composition, carotenoid and polyphenol contents and hydrophilic antioxidant capacity of fresh peach palm (Bactris gasipaes) fruit was studied with a view to its exploitation as a potential source of bioactive compounds. The variability present in five batches of peach palm fruit obtained from two regions in Costa Rica: Tucurrique (T) and Pérez Zeledón (PZ), was studied. Significant differences were found for fruit weight, length and width amongst the batches studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 17 publications
1
11
0
1
Order By: Relevance
“…Table 3 in comparison with Singh's research data [29], the content of total phenolic compounds was 2.98mg GAE/100g and antioxidant capacity of 38.76µmol TROLOX/100g, results close to those obtained in this investigation. In contrast, Rojas-Garbanzo et al [30], reported averages of 54mg to 106mg GAE/100g, with an average antioxidant capacity of 37±7.0µmol of Trolox Equivalents (TE)/g. The organic action of the bioactive compounds present in pupunha, including total phenolics, carotenoids and antioxidant capacity (Table 3) is closely related to human growth and development and protection of the body against oxidative stress, caused by Reactive Oxygen Species (ROS) that damage cellular components such as proteins, lipids, Deoxyribonucleic Acid (DNA) and Ribonucleic Acid (RNA), through their oxidation [31,32].…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Table 3 in comparison with Singh's research data [29], the content of total phenolic compounds was 2.98mg GAE/100g and antioxidant capacity of 38.76µmol TROLOX/100g, results close to those obtained in this investigation. In contrast, Rojas-Garbanzo et al [30], reported averages of 54mg to 106mg GAE/100g, with an average antioxidant capacity of 37±7.0µmol of Trolox Equivalents (TE)/g. The organic action of the bioactive compounds present in pupunha, including total phenolics, carotenoids and antioxidant capacity (Table 3) is closely related to human growth and development and protection of the body against oxidative stress, caused by Reactive Oxygen Species (ROS) that damage cellular components such as proteins, lipids, Deoxyribonucleic Acid (DNA) and Ribonucleic Acid (RNA), through their oxidation [31,32].…”
Section: R E S U L T S a N D Discussionmentioning
confidence: 91%
“…In research studies using the same species of pupunha, with different origins, Rojas-Garbanzo et al [30], with peach palm fruits from Costa Rica, found an average of 1.65µg/g of total carotenoids in the peach palm pulp. In turn, Hempel et al [36] obtained a maximum content of 139.00µg/g in varieties of red pupunha also from Costa Rica.…”
Section: Observing the Data Inmentioning
confidence: 99%
“…Even though the contents of phenolic compounds are much higher than carotenoids in peach palm fruits, the fruits are mostly known by their attractive colours due to the presence of carotenoids, and scientific information concerning phenolic compound contents are scarce (Rojas-Garbanzo et al, 2016. There are studies regarding classical solid-liquid extraction techniques of carotenoids and phenolic compounds from peach palm fruits (Basto et al, 2016;Rojas-Garbanzo et al, 2016;Matos et al, 2019). However, the application of UAE was investigated only for extracting total carotenoids from dried peels using vegetable oils (soybean and sunflower) (Ordóñez- Santos et al, 2015;Ordoñez-Santos et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…A pupunha possui qualidades nutritivas e energéticas, sendo rica, principalmente, em vitamina A, cálcio, fósforo, ferro, complexo B, carboidratos (principalmente amido) e gorduras insaturadas (GIRÓN et al, 2017). Corroborando com esta afirmativa, Rojas-Garbanzo et al (2016) também destacam o potencial do fruto em termos de propriedades antioxidantes.…”
Section: Introductionunclassified